2020
DOI: 10.1055/a-1116-2102
|View full text |Cite
|
Sign up to set email alerts
|

The DIEP Flap as Well-established Method of Choice for Autologous Breast Reconstruction with a Low Complication Rate – Retrospective Single-centre 10-Year Experience

Abstract: Background Breast cancer is the most common cancer affecting women in Germany. Despite breast-conserving therapy (BCT) being carried out in almost 70% of cases, a high number of women still require complete mastectomy. Prophylactic mastectomy is also indicated for women with a BRCA 1/2 gene mutation. In addition to implant-based heterologous breast reconstruction, autologous breast reconstruction using a DIEP flap has been found to be beneficial, particularly for patients who had prior radiotherapy. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
(25 reference statements)
1
4
0
3
Order By: Relevance
“…This one-step procedure is shown to be safe, feasible and well accepted [ 133 ]. The combined approach is positive in terms of cost-effectiveness ([ 152 , 153 ]), particularly for patients who had prior radiotherapy. Free flap surgery is an excellent option for autologous breast reconstruction, with low rate of donor site morbidity and low complication rate [ 153 ].…”
Section: Surgical Procedures Associated With Female With Brca Mutationmentioning
confidence: 99%
“…This one-step procedure is shown to be safe, feasible and well accepted [ 133 ]. The combined approach is positive in terms of cost-effectiveness ([ 152 , 153 ]), particularly for patients who had prior radiotherapy. Free flap surgery is an excellent option for autologous breast reconstruction, with low rate of donor site morbidity and low complication rate [ 153 ].…”
Section: Surgical Procedures Associated With Female With Brca Mutationmentioning
confidence: 99%
“… 14 As to age at surgery, smoking status, diabetes mellitus, and neoadjuvant chemotherapy numerous studies have concluded that there is no significantly higher risk of seroma formation linked to the factors, which corresponds to our findings. 15 16 17 21 It must be stated, however, that some of these studies did not analyze seroma as a donor site complication separately but rather as part of a group of possible complications (mostly in the form of minor complications). Additionally, the low incidence of smokers ( n = 17) and diabetics ( n = 3) in our study is a limiting factor.…”
Section: Discussionmentioning
confidence: 99%
“…50 % der Implantatverluste seien dabei in den ersten 2 Jahren aufgetreten. Im Gegensatz hierzu ist nach einer mikrochirurgischen autologen Rekonstruktion ein Komplettversagen, d. h. ein totaler Lappenverlust von in der Regel lediglich 1-2 % [82] zu verzeichnen und sollte immer in die ausführliche Patientinnenberatung hinsichtlich der Wahl der Rekonstruktionsmethode einfließen. Ein wertvoller praktischer Gesichtspunkt im Rahmen der Diskussion, ob die heterologe oder autologe Vorgehensweise bei der Rekonstruktion zu favorisieren ist, stellt bei initialer Verwendung eines Implantats die Möglichkeit dar, alle anderen Optionen inklusive autologer Rekonstruktion für spätere Rekonstruktionsalternativen weiterhin offen zu haben.…”
Section: Verzögerte Autologe Brustrekonstruktion In Kombination Mit Pmrtunclassified